Laicità e mondo classico. Riflessioni introduttive - Franco Cambi (Firenze University Press, 2011)
The author reflects on the concept of secularism from the ancient culture up to the modern and contemporary age. He focuses on four forms and borders of investigation (Hellenism, Christianity, St. Augustine to modern times) and he points out that today is still very important to reflect on the historical and political origins of this category.